Angiotensin Converting Enzyme Inhibitors (ACEIs) Decrease the Progression of Cardiac Fibrosis in Rheumatic Heart Disease Through the Inhibition of IL-33/sST2 - Ambari, Ade M.; Setianto, Budhi; Santoso, Anwar; Radi, Basuni; Dwiputra, Bambang; Susilowati, Eliana; Tulrahmi, Fadilla; Doevendans, Pieter A.; Cramer, Maarten J. (Frontiers in Cardiovascular Medicine, 2020)
Rheumatic heart disease (RHD) is common in developing countries and poses a big medical challenge and burden. The pathogenesis of RHD is influenced by the triad of host, agent, and environment. Autoantigens generated from Group A Streptococcus (GAS) infection are captured by the resident dendritic cells (DCs) in the heart's valvular endothelium. DCs differentiate into antigen presenting cells (APC) in the valve interstices. APC induces activation of autoreactive T cells, which triggers inflammation and tissue fibrosis. Cardiac fibrosis is promoted through the activation of Mitogen activated protein kinases (MAPKs) and its downstream signaling, including its interaction with transforming growth factor-β (TGF-β) and Smad proteins. TGF-β-induced phosphorylation of Smad2 complexes with Smad3 and Smad4, and translocates into the nucleus. Angiotensin II enhances the migration, maturation, and presentation of DC. In RHD, Angiotensin II induces fibrosis via the stimulation of TGF-β, which further increases the binding of IL-33 to sST2 but not ST2L, resulting in the upregulation of Angiotensin II and progression of cardiac fibrosis. This cascade of inflammation and valvular fibrosis causes calcification and stiffening of the heart valves in RHD. Angiotensin converting enzyme inhibitors (ACEIs) inhibit Angiotensin II production, which in turn decreases TGF-β expression and the onset of overt inflammatory response. This condition leads to a reduction in the sST2 as the decoy receptor to “steal” IL-33, and IL-33 binds to ST2L and results in cardioprotection against cardiac fibrosis in the pathogenesis of RHD.